2012
DOI: 10.1111/j.1365-2648.2012.05948.x
|View full text |Cite
|
Sign up to set email alerts
|

Health, lifestyle, belief and knowledge differences between two ethnic groups with specific reference to tobacco, diet and physical activity

Abstract: Health risk behaviour and morbidity are different between the two ethnic groups. Gender, age, educational level, beliefs, attitudes and knowledge do not explain these differences. Health promotion that aims to improve knowledge will probably not work and innovative methods are needed to improve health in high risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This result has been provided by the research conducted by Fernandez et al among Asian Indians living in Australia [26], which raised awareness on the subject of coronary heart disease risk, or research by Anthony et al [27] on the lifestyles of ethnic groups. However, further research will be necessary, which should focus on diseases of the cardiovascular system among Catholics and SDA as well as other religious or ethnic groups.…”
mentioning
confidence: 78%
“…This result has been provided by the research conducted by Fernandez et al among Asian Indians living in Australia [26], which raised awareness on the subject of coronary heart disease risk, or research by Anthony et al [27] on the lifestyles of ethnic groups. However, further research will be necessary, which should focus on diseases of the cardiovascular system among Catholics and SDA as well as other religious or ethnic groups.…”
mentioning
confidence: 78%
“…The main behavioral risk factors of non-contagious diseases include smoking, unhealthy diet, physical inactivity, and alcohol consumption and physiological risk factors for these diseases include high blood pressure, high cholesterol, and overweight or obese [1] . A global outbreak of CVDs relates to lifestyle risk factors such as smoking, unhealthy diet, physical inactivity, and alcohol consumption [10,11] . A study examining taking care of risk factors for non-contagious diseases has studied 5 risk factors, including daily smoking, low intake of fruits and vegetables, inactivity, overweight and obesity, and high blood pressure among people aged 15 to 64 years old in its last review around the country in 2009; This study indicated that 96.7% of people have at least one risk factor for CVDs and 21.64% of people aged 15 to 44 years old and 52.9% of people aged 45 to 64 years old have at least 3 risk factors out of 5 risk factors for CVDs; in other words, they are at high risk [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The livelihood and lifestyle of rural communities of Africa are quite synonymous. These similitudes could be found in aspects such as festivals, customs and farming practices, which are predominantly the subsistence mode of farming (Anthony et al, 2012;Nussbaum, 2003;Bigombe & Khadiagala, 2004). Farming was the main source of livelihood amongst several rural communities of Africa in the 60's.…”
Section: Introduction mentioning
confidence: 99%